Inquiry Based Learning STEM Teaching Materials to Improve Students’ Thinking Skills in Stoichiometry - Panggabean, Freddy Tua Musa; Silitonga, Pasar Maulim; Sutiani, Ani; Purba, Jamalum; Gultom, Risdo (Jurnal Tadris Kimiya, 2023)
In stoichiometry learning process, mostly educators focus on calculations. Students are not invited to think more critically about stoichiometry application in life. This constraint makes teachers have to develop new learning models, including Inquiry Based Learning (IBL) model, and Science, Technology, Engineering, Mathematics (STEM) based on chemical literacy. This study aims to develop general chemistry teaching materials on stoichiometry using IBL and STEM models based on chemical literacy that are feasible (valid) and capable of improving students' LOTS and HOTS abilities. The development model used is the ADDIE model, with research subjects of 34 students. The result shows that stoichiometry teaching materials using the IBL STEM model based on chemical literacy are valid (feasible) to be applied in learning with an average score of 4.42 for the material aspect and 4.55 for the design aspect. The developed teaching materials have been proven to significantly improve students’ LOTS and HOTS abilities.